THE ARAB SPRING AND CIVIL-MILITARY RELATIONS: A PRELIMINARY ASSESSMENT - Segell, Glen (Scientia Militaria - South African Journal of Military Studies, 2013)
The ‘Arab Spring’ refers to the wave of civil unrest that covered countries with predominant Moslem populations in North Africa, the Middle East and the Arabian Peninsula, which started late 2010 in Tunisia. The unrests quickly spread across the region, giving rise to the notion of a single inter-related event. However, the results and outcome in each country have been different. This is because each and every country had its own unique political system and unique institutions of state with different relations between power elites. Two institutions of state had prime importance in this political system. These were the executive and the military. In each there was only one important person, the state leader be he president, king, prime minister, emir or sheik or the chief of the armed forces. This article describes that a major cause for the different results and outcomes in each country was determined by the prevailing relations between them, i.e. the civil-military relations.